THE EFFECT OF GIVING PROBIOTICS FROM PROCESSED BANANA STEMS TO INCREASE THE SURVIVAL OF PANGAS CATFISH SEEDS IN THE TRANSPORTATION PROCESS - Fitriani, Emita; Istyadji, Maya; Yulinda, Ratna (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2022)
The high mortality or death during the transportation process is caused by the fact that catfish fry are stress-prone fish and have fast metabolism. Handling the problem of high mortality in the process of transporting catfish seeds requires alternative probiotics from banana stems because banana stems contain saponins, flavonoids, alkaloids, and tannins. This study aims to determine the effect of giving probiotics from processed banana stems to increase the survival of catfish seeds in the 6-hour transportation process, the study used a randomized block design (RBD) with 4 treatments, namely giving fermented banana stem probiotics (T1), banana stem probiotics without fermentation (T2), commercial probiotics (T3), without probiotics (C) with 3 repetitions. The results showed that giving banana stem probiotics had an effect based on the ANOVA test of 0.00 <0.05 and in Duncan's test there was a significant difference in each treatment. In the study the effect of probiotics was seen from the still ideal water quality, fish behavior during the transportation process and survival rate (SR). SR of each treatment was (T1) 90%, 86%, 84%, (T2) 98%, 98%, 96%, (T3) 88%, 90%, 84% , (C) 20%, 28%, 20%. Giving probiotics from processed banana stems without fermentation (T2) had the best effect on the survival of catfish seeds in the transportation process.